Impairment of cycling capacity in the heat in well-trained endurance athletes after high-intensity short-term heat acclimation - Reeve, T.; Gordon, R.; Laursen, P. B.; Lee, J. K. W.; Tyler, C. J. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To investigate the effects of short-term, high-intensity interval-training (HIIT) heat acclimation (HA). Methods: Male cyclists/triathletes were assigned into either an HA (n = 13) or a comparison (COMP, n = 10) group. HA completed 3 cycling heat stress tests (HSTs) to exhaustion (60% Wmax; HST1, pre-HA; HST2, post-HA; HST3, 7 d post-HA). HA consisted of 30-min bouts of HIIT cycling (6 min at 50% Wmax, then 12 × 1-min 100%-Wmax bouts with 1-min rests between bouts) on 5 consecutive days. COMP completed HST1 and HST2 only. HST and HA trials were conducted in 35°C/50% relative humidity. Cycling capacity and physiological and perceptual data were recorded. Results: Cycling capacity was impaired after HIIT HA (77.2 [34.2] min vs 56.2 [24.4] min, P = .03) and did not return to baseline after 7 d of no HA (59.2 [37.4] min). Capacity in HST1 and HST2 was similar in COMP (43.5 [8.3] min vs 46.8 [15.7] min, P = .54). HIIT HA lowered resting rectal (37.0°C [0.3°C] vs 36.8°C [0.2°C], P = .05) and body temperature (36.0°C [0.3°C] vs 35.8°C [0.3°C], P = .03) in HST2 compared with HST1 and lowered mean skin temperature (35.4°C [0.5°C] vs 35.1°C [0.3°C], P = .02) and perceived strain on day 5 compared with day 1 of HA. All other data were unaffected. Conclusions: Cycling capacity was impaired in the heat after 5 d of consecutive HIIT HA despite some heat adaptation. Based on data, this approach is not recommended for athletes preparing to compete in the heat; however, it is possible that it may be beneficial if a state of overreaching is avoided.